Relationship Between Violence, Empathy and Aggression - Syeda Nadia Shah (Peshawar Journal of Psychology and Behavioral Sciences, 2015)
One of the basic purpose of this study is to determine gender differences and relationship of violence with that of empathy and aggression. The total sample of the study contained sixty-four (N=64) University students with the age range on 20-25 years. The sample included thirty-two (n=32) male and thirty-two (n=32) female students of University of Peshawar. The results revealed the significant difference on violence between male and female university students males scored significantly higher on violence scale as compared to females. A negligible negative correlation was found between violence and empathy. It was concluded from the finding of the present study that males are more violent than females but there is no significant relation between violence, empathy and aggression.